Comparative analysis of the quality indicators of bread made of composite flour using ozonated water - Камила Әділбекқызы Нәсіпқали (Алматы технологиялық университетінің хабаршысы, 2022)
According to the First President of Kazakhstan, it is important to exclude any possibility of food shortages. In this regard, the primary task of the population is to create innovative technologies for the successful promotion and avoidance of food shortages. Bread is one of the most important food products in Kazakhstan. Consequently, the main task of the population of the bakery industry today is the creation of innovative technologies for functional food products. The article presents the results of an organoleptic study of the bread of innovative preparation using composite flour and ozonated water.